Growth performance and gut health of Murrah buffalo calves fed with developed novel synbi- otic formulation - Antony J. Thanippilly; Sachin Kumar; Vinay V. Varada; Nitin Tyagi; Ashish K. Samanta (Revista Científica)
The present study aimed to develop a novel synbiotic formulation by screening different prebiotics as a substrate for autochthonous Lactobacillus spp. and studying their effects on the gut health and performance of buffalo calves. Ligilactobacillus salivarius BF17 (NCBI GenBank Accession No-MG966326), a potential probiotic previously isolated from Murrah buffalo calves, was chosen and evaluated for the best prebiotic substrate by screening five different prebiotics (fructo oligosaccharides, mannan oligosaccharides, inulin, corn dextrin, and wheat dextrin). Then, 23 neonatal buffalo calves were selected for 90 days and randomly divided into four groups, with five animals in the control group and six each in the treatment group. The groups were as follows: 1) control (CON) fed basal diet alone; 2) prebiotic group (PRE) supplemented with chicory powder (a natural source of inulin) at eight g/d/calf; 3) probiotic group (PRO), supplemented with milk fermented with L. salivarius BF17 having 108 CFU/g/d/calf and 4) synbiotic group (SYN) supplemented with both prebiotic and probiotic. All the calves had ad libitum access to a basal diet, having calf starter (from the second week onwards), green forage (maize and sorghum), and fresh, clean water throughout the experimental period. The calf starter (concentrate mixture) was formulated using quality ingredients comprising maize (28%), bajra (5%), groundnut (10%), soybean meal (15%), mustard oil cake (13%), wheat bran (15%), rice polish (11%), vitamin and mineral premix (2%), salt (1%). The body weight and structural measurements (body length, wither height, heart girth) were recorded fortnightly. Feed intake and residue were also measured during a digestion trial to determine the digestibility of various nutrients. Fecal samples were collected at fort-nightly intervals to analyze fecal pH, lactate, ammonia, and short-chain VFA. Microbiota enumeration of health-promoting (lactobacilli and bifidobacterial) and health-negative (coliform and clostridium) was enumerated by colony-forming method to assess gut health. Results indicated that inulin showed the highest (p<0.05) prebiotic index and prebiotic activity score by FOS, MOS, and dextrins; hence, inulin was chosen for synbiotic formulation with L. salivarius BF17. Chicory root powder was taken as a natural and cheaper source of inulin for animal feeding. The inulin content of chicory powder was estimated using the spectrophotometric method and found to be 57.5%. The final body weight of buffalo calves was higher (p<0.05) in SYN, followed by PRE and PRO, compared to CON. Structural growth measurements were also higher (p<0.05) in all the supplemented groups compared to the control group. A simultaneous increase (p<0.05) in Lactobacillus and Bifidobacterium populations and a decrease (p<0.05) in coliforms were observed in the synbiotic and probiotic-supplemented groups. The fecal biomarkers altered favorably, significantly in all the supplemented groups compared to the control group. Overall, it was concluded that inulin was found to be the best prebiotic for synbiotic formulation with Ligilactobacillus salivarius BF17, and supplementation of prebiotic, probiotic, and synbiotic improved the growth performance and gut health parameters in Murrah buffalo calves, however, the results were found to be better in the synbiotic group.